Beyond sustainability: The ESG performance relationship on earnings management and tax avoidance - Muhammad Hammam Al Hashfi (Directorate General of Taxes, 2024)
The growing emphasis on environmental, social, and Governance (ESG) performance in the business landscape has triggered interest in exploring company practices beyond financial strategies, such as earnings management and tax avoidance while highlighting their role in long-term sustainability. This study examines how the complex relationships between ESG performance, earnings management, and tax avoidance contribute to comprehensive firm activities, specifically exploring the impact of a firm's commitment to ESG on its decisions regarding earnings management and tax avoidance. This study uses 60 companies over five years, between 2018 - 2022, and EViews 12 software to conduct descriptive statistics, panel models, classical assumption tests, and hypothesis testing. This study unveils a significant negative relationship between ESG performance and tax avoidance and negative relationships between ESG performance and earnings management through accruals and absolute discretion. Investors and stakeholders may have greater confidence in companies with high ESG performance, as they are less likely to engage in tax avoidance, accrual, and actual earnings management practices that could compromise financial sustainability.